P242 The order effect of experimental oesophageal acidification on cough reflex sensitivity in chronic cough patients and healthy volunteers. (12th November 2015) - Valdramidou, D; Sumner, H; Hilton, E; Whiteside, S; Smith, JA
Abstract : Background: One of the mechanisms thought to be involved in the triggering of chronic cough is gastroesophageal reflux. We aimed to compare the effects of oesophageal acid infusion on cough reflex sensitivity in chronic cough (CC) patients with healthy volunteers (HV). Method: In a randomised, double–blind, placebo-controlled, crossover study, 0.15 M hydrochloric acid/saline was infused in the distal oesophagus of each subject. Each infusion treatment was separated by a washout period of at least 7 days. Single dose inhalation capsaicin challenge (C5 ) was used to measure cough reflex sensitivity before (baseline), immediately after (t = 0 mins) and 90 min, 180 min and 24 hrs post infusion. Data were analysed using Generalised Estimating Equation (GEE) models. Results: Ten CC patients (mean age 56.0 ± 11.0 years, 8 females) and twelve HV (mean age 26 ± 8.3 years, 7 females) completed the study. Overall, CC patients had a more sensitive cough reflex than HV (geometric mean ratio 0.46; ratio 0.05, Table 1 ). Furthermore, there was a significant order effect (acid-saline vs saline-acid); CC patients appeared to be sensitised to acid infusion when given first (p-value = 0.039), but not second (p-value = 0.245), whereas HV cough responses were not influenced by the infusion order (all p-values > 0.05). Conclusions: In our experience, distal oesophageal acid infusion did not sensitise the cough reflex in either CC patients or HV. Notably, the order of the infusions heavily influenced the cough responses of CC patients compared to HV. Future study designs need to be cognisant of order effects and if cross-over designs are used, test for the presence of these.